The Imperative of Health : Public Health and the Regulated Body - Lupton, Deborah (SAGE Publications Ltd, 1995)
`A good history of public health developments, primarily in Australia and England, the book is a continuation of debate among health education profession over the status of any or all health education ""truths""' - Choice.